What can be expected to be seen in a Neurology ward? Eleven-year experience in a Brazilian university hospital - Daniel Gabay MOREIRA; Enedina Maria Lobato de OLIVEIRA; Fernando Morgadinho dos Santos COELHO; Henrique Ballalai FERRAZ; Silvio FRANCISCO; Vanderci BORGES; Denis Bernardi BICHUETTI (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Neurological disorders are significant causes of morbidity and mortality worldwide. However, data about general neurological inpatient admissions in Brazil is limited. Objective: To investigate the prevalence of neurological disorders according to disease group and lesion site among patients admitted to a general Neurology ward. Methods: This was an observational and descriptive study. The hospital discharge database for the Neurology ward was surveyed in accordance with the International Classification of Diseases, 10th edition (ICD-10), from September 2008 to October 2019. The final diagnosis was classified into neurological disorder groups and site. Results: Overall, 2,606 clinical neurological patient files were included, with mean length of hospitalization of 16.7 days and a total of 325 readmissions (12.5%). The overall mortality rate in the ward was 3.8% (100 patients). Among all the diagnoses, cerebrovascular disease was the most prevalent (45.8%), followed by inflammatory disorders (22.2%). The brain was the most common lesion site (66.0%), followed by peripheral nerves (10.0%) and meninges and cerebrospinal fluid (7.7%). Conclusions: The disease pattern upon admission showed that a majority of the cases consisted of cerebrovascular disorders and that the brain was the most frequently affected structure, although we observed that a wide variety of cases were admitted, encompassing all neurological disorders.